ANTIBACTERIAL ACTIVITIES OF EXTRACT AND ACTIVE FRACTION OF MADEIRA VEIN [Anredera cordifolia (Ten.) v. Steenis] LEAVES AND ITS INFLUENCE ON SEVERAL ANTIBIOTICS - Putu Eka Leliqia, Ni
The use of antibiotics played an important role in the infectious diseases therapy. However, uncontrolled long-term use or improper use of antibiotic led to bacterial resistance. Therapeutic options for this case were extremely limited, as well the prospect for next generation antibacterial drug development. Chemical compounds from plant that had antibacterial activity became an alternative and a starting point of new antibacterial inventions. Ethanol leaves extract of madeira vine [Anredera cordifolia (Ten.) v. Steenis] was proven to inhibit the growth of some Gram-positive and Gram-negative bacteria such as Bacillus cereus, Bacillus subtilis, Escherichia coli, Pseudomonas aeruginosa, Methicillin-Resistant Coagulase-Negative Staphylococcus, and Methicillin-Susceptible Staphylococcus aureus (MSSA). Chemical compounds such as tannin, saponin, alkaloid, triterpenoid, and flavonoid found in madeira vine leaves were proven to have antibacterial activity. Moreover, safety study of ethanolic leaves extract of madeira vine by acute and subchronic study revealed that madeira vine leaves extract showed no toxicity and abnormality in rats. One way to find active compounds from plants is by using bioassay-guided fractionation method. By knowing the activity of a chemical compound group which was contained in the fraction, a compound isolation could be conducted to obtain a single active compound. Research on the active fraction of madeira vine leaves which was responsible for antibacterial activity were not reported. However, several studies of alleged compounds found in madeira vine leaves such as ursolic acid had antibacterial activity. The use of antibiotics combination which was given simultaneously had become a therapeutic strategy. Clinical administration of antibacterial combination based on in vitro test result which gave a synergistic effect in preventing the growth of pathogen bacteria. Amoxicillin, tetracycline HCl, and ciprofloxacin were antibiotics commonly prescribed to treat the infection and its combination with several plants extract or chemical compounds showed a synergistic effect. However, besides the potential benefit of a synergistic effect between antibacterial vii agents, there was also a risk of antagonistic effects due to the antibacterial agent which might affect the activity of other agents. This study aimed to examine the antibacterial activities of extract and fraction of madeira vine leaves; to determine the effect of ethanol extract and active fraction of madeira vine leaves towards amoxicillin, tetracycline HCl, and ciprofloxacin activities; to determine working site of ethanol extract and active fraction of madeira vine leaves on bacterial cell, also the effect of ethanol extract on antibiotic activity based on scanning electron microscope (SEM) and transmission electron microscope (TEM) observations; and to test the safety of ethanol extract of madeira vine leaves with one of the antibiotics that gave synergistic effect by using subchronic toxicity test. Crude drug of madeira vine [Anredera cordifolia (Ten.) v. Steenis] leaves was collected from Manoko-Lembang, West Java, Indonesia. The crude drug was extracted using two methods. The first extraction method was performed by reflux using 96% ethanol and obtained a thick extract (EE1). EE1 was added with hot water then filtered while still hot. Filtrate was fractionated by liquid-liquid extraction method using n-hexane and ethyl acetate, therefore obtained n-hexane, ethyl acetate, and aqueous fractions. The second extraction method was conducted by reflux using increasing polarity solvents such as n-hexane, ethyl acetate, and ethanol 96%, consecutively. The n-hexane, ethyl acetate, and ethanol extract (EE2) were obtained by this method. Extract with the best antibacterial activity was fractionated by the preparative thin layer chromatography (TLC) method. Phytochemical screening was performed on EE1 and its fractions as well as the extract from the second extraction, followed by chromatographic profile examination using ursolic acid, oleanolic acid, apigetrin, and rutin as marker compounds. The madeira vine leaves extracts and fractions were tested for their antibacterial activities using microdilution method against the growth of Grampositive bacteria i.e. MSSA (ATCC 6538), MSSA 1, MRSA (Methicillin-Resistant Staphylococcus aureus) 23, B. cereus (ATCC 11778), B. subtilis (ATCC 6633), and Gram-negative bacteria such P. aeruginosa (ATCC 9027), E. coli (ATCC 8939), E. coli H7 (O156), and clinical isolate of Extended-Spectrum Beta-Lactamase- Producing E. coli. Antibacterial activity was determined based on the minimum inhibitory concentration (MIC) value. Study of the combination of ethanol leaves extract of madeira vine or its active fraction with antibiotics (amoxicillin, tetracycline HCl, and ciprofloxacin) were tested by using checkerboard method. Combination effect was determined based on the fractional inhibitory concentration index. The antibacterial working site of ethanol extract, active fraction, and the combination of ethanol extract and antibiotic were observed by SEM and TEM. Combination of EE1 and amoxicillin was tested for its safety with subchronic toxicity test in Wistar rats. There were 4 test groups in this test: control group (CMC Na 0.3%), EE1 (865 mg/kg bw) and amoxicillin (135 mg/kg bw) combination group (total dose of 1 g/kg bw), control satellite group, and satellite group of combined drugs. Administration of test preparation in rats was done for 90 days. On the 91 st day, the urine characteristics, hematology, organ index, blood biochemistry, and histopathology from the control group and combination groups were observed. While the satellite group was allowed to stand for 30 days after the viii administration of the test preparation, and on the 120 th day, satellite groups were observed for its urine characteristics, hematology, organ index, blood biochemistry, and histopathology. Data were analyzed by using one-way ANOVA- LSD. The significance value was set on p<0.05. Saponins were found in aqueous fraction and ethanol extract from both extraction methods. Flavonoid and alkaloid were seen in most extracts and fractions, except in n-hexane fraction and n-hexane extract. All extracts and fractions contained steroid/triterpenoid. Thin layer chromatogram of madeira vine leaves extract and fraction indicated the presence of ursolic acid and oleanolic acid in EEI, n-hexane fraction and n-hexane extract. EE1, ethyl acetate fraction, aqueous fraction, and ethyl acetate extract contained apigetrin and rutin, whereas EE2 only contained apigetrin. Ethanol extract, n-hexane fraction, and ethyl acetate fraction from the first method extraction had antibacterial activity against MSSA (ATCC 6538), MRSA, B. subtilis, and B. cereus (MIC 256-512 ?g/mL). However, n-hexane and ethyl acetate extracts from the second method extraction had better activities than extract and fraction from the first method, which could inhibit the growth of Gram-positive and Gram-negative bacteria, such as MSSA (ATCC 6538), MRSA, B. subtilis, P. aeruginosa, and E. coli (MIC 256-512 ?g/mL). The n-hexane extract from the second method extraction had the highest antibacterial activity. Furthermore, the n-hexane extract was fractionated by preparative TLC with silica gel GF254 as stationary phase, toluene-ethyl acetate-formic acid (35:15:1) as mobile phase and 16 fractions were obtained, then their antibacterial activity was tested against 6 test bacteria, i.e MSSA (ATCC 6538), MSSA 1, MRSA, B. subitilis, P. aeruginosa, and E. coli. Fraction 1 (Rf 0.12), 5 (Rf 0.48), 6 (Rf 0.51), 8 (Rf 0.57), 10 (Rf 0.66), 14 (Rf 0.86), and 16 (Rf 0.96) showed antibacterial activities against MSSA (ATCC 6538) (MIC 256-512 ?g/mL). Fraction 8, 10, 12 (Rf 0.77), 13 (Rf 0.82), and 16 expressed antibacterial activities against MSSA 1 (MIC 256-512 ?g/mL). Fraction 1, 5, 8, and 9 (Rf 0.61) presented antibacterial activities against B. subtilis (MIC 512 ?g/mL). Fraction 8 showed antibacterial activity against E. coli (MIC 512 ?g/mL). None of the fractions showed antibacterial potential against P. aeruginosa. Fraction 8 exhibited the highest activity compared to the other fractions and was proposed as the active fraction of madeira vine leaves. A chromatographic profile examination of active fraction with silica gel GF254 as the stationary phase and toluene-acetone-formic acid (11:16:0.2) as mobile phase followed by spraying with Liebermann-Burchard reagent, showed that this fraction contained triterpenoid compounds. Ethanol extract from the first method extraction (EE1) increased the antibacterial activity of the antibiotics in some of the bacteria test indicated by the synergistic and additive effects when extracts and antibiotics combined. The combination of EE1 with amoxicillin and ciprofloxacin had a synergistic effect on inhibition of MSSA (ATCC 6538) and MSSA 1 growth. Only the combination of EE1 with amoxicillin gave synergistic effect on B. subtilis growth inhibition. The combination had no effect on E. coli growth, except the combination of EE1 and ciprofloxacin. The combination of EE1 with all antibiotics gave an additive effect on MRSA 23 growth inhibition. In addition, a combination of EE1 with tetracycline HCl also had an additive effect on MSSA and B. subtilis. ix The active fraction of madeira leaves increased antibiotics inhibition of several test bacteria growth, indicated by its synergistic or additive effects. The combination of the active fraction with all antibiotics had a synergistic effect on B. subtilis bacteria growth inhibition. The synergistic effect on MSSA (ATCC 6538) growth inhibition was also shown when the active fraction was combined with tetracycline HCl. The combination had no effect on E. coli growth, except the active fraction with ciprofloxacin combination. The combination of the active fraction with amoxicillin showed an additive effect on MSSA growth inhibition. Scanning electron microscope observation was done for MSSA (ATCC 6538) and B. subtilis cells which were exposed by EE1, active fraction, or combination of EE1 and antibiotics that gave synergistic effect. The results showed both bacterial cells undergo changes in shape or morphology of cell wall. The synergistic effect was shown by the combination of EE1 and antibiotics. Bacterial cells experienced morphological changes when exposed to ¼ MIC of EE1 and antibiotics with a concentration of ?¼ MIC. Based on the SEM observation, the mechanism of action exerted by the test sample was suspected to be related to their ability to inhibit the biosynthesis of the bacterial cell wall. This result is confirmed by TEM's observations that EE1 caused cell wall damage, eventually caused leakage of the cellular contents. The cell wall damage was also seen in MSSA cells (ATCC 6538) that exposed to EE1 and amoxicillin. Subchronic toxicity test results showed that combination of EE1 (865 mg/kg bw) and amoxicillin (135 mg/kg bw) in Wistar rats did not induce mortality, behavioral changes, and motoric activities. Although an increased in body weight during test were observed on the combination group and the control group, no statistical difference appeared between them. This suggested that giving the combination did not increase the appetite of rats. The combination administration did not cause significant changes in the urine characteristics, hematology, organ index, blood biochemistry, as well as microscopy of the rats’heart, liver, kidney, spleen, and lung in rats. In conclusion, the information learned based on the results of this study is the use of antibiotics in conjunction with steeping madeira leaves or capsules is thought to increase its efficacy and declared safe based on the results of toxicity tests.